Exploring sex differences in autistic traits: A factor analytic study of adults with autism. (August 2017) - Grove, Rachel; Hoekstra, Rosa A; Wierda, Marlies; Begeer, Sander
Research has highlighted potential differences in the phenotypic and clinical presentation of autism spectrum conditions across sex. Furthermore, the measures utilised to evaluate autism spectrum conditions may be biased towards the male autism phenotype. It is important to determine whether these instruments measure the autism phenotype consistently in autistic men and women. This study evaluated the factor structure of the Autism Spectrum Quotient Short Form in a large sample of autistic adults. It also systematically explored specific sex differences at the item level, to determine whether the scale assesses the autism phenotype equivalently across males and females. Factor analyses were conducted among 265 males and 285 females. A two-factor structure consisting of a social behaviour and numbers and patterns factor was consistent across groups, indicating that the latent autism phenotype is similar among both autistic men and women. Subtle differences were observed on two social behaviour item thresholds of the Autism Spectrum Quotient Short Form, with women reporting scores more in line with the scores expected in autism on these items than men. However, these differences were not substantial. This study showed that the Autism Spectrum Quotient Short Form detects autistic traits equivalently in males and females and is not biased towards the male autism phenotype.